A promising novel material-light-cured wound closure adhesives promote wound healing after pilonidal sinus open surgery: a Case Report - Ni, Jiachun; Yang, Yiheng; Liu, Qinyuan; Deng, Yu; Zhou, Renjie; Zhu, Linyong; Li, Ying; Wang, Zhenyi; Han, Changpeng (Frontiers in Bioengineering and Biotechnology, 2025)
Background/objectivesPilonidal sinus disease (PSD), a common sacrococcygeal infectious disease, is characterized by sacrococcygeal swelling, pain, sacrococcygeal midline pits, sinus containing hair. Surgery is the main treatment for PSD. Although closure surgery reduces wound healing time, it has a high recurrence rate. Open surgery is the most effective procedure for treating PSD with reduced recurrence rates, but at the cost of large wounds, prolonged healing times, cumbersome care and long-term inactivity. Therefore, how to balance postoperative recurrence with prolonged wound healing time is a critical issue for clinicians. Herein, we introduced a novel material called light-cured wound closure adhesives, which is characterized by strong tissue binding strength, high biocompatibility, prominent wound healing capability.MethodsWe present the case of a 22-year-old male with PSD who underwent open surgery. The light-cured wound closure adhesives were first applied to postoperative wound. We observed wound healing status, wound Numeric Rating Scale (NRS) pain scores, adverse events including exudation, infection, allergy, meanwhile documented the use of analgesics during follow-up period.ResultsThe wound healed at postoperative day 37, much shorter than that reported in the previous literature. The NRS pain scores are low. Adverse events includes excessive exudation, pruritus, granulation hyperplasia.ConclusionLight-cured wound closure adhesives showed excellent pro-healing capabilities and brilliantly solved the paradox between high recurrence rate and prolonged wound healing time of PSD.